2021
DOI: 10.1186/s12872-021-02286-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CAD-RADS classification by coronary CTA in patients with suspected CAD

Abstract: Background The study sought to compare Coronary Artery Disease Reporting and Data System (CAD-RADS) classification with traditional coronary artery disease (CAD) classifications and Duke Prognostic CAD Index for predicting the risk of all-cause mortality in patients with suspected CAD. Methods 9625 consecutive suspected CAD patients were assessed by coronary CTA for CAD-RADS classification, traditional CAD classifications and Duke Prognostic CAD In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Our previous study has showed that the prevalence of non-obstructive CAD is higher than that of obstructive CAD 13 , which is consistence with other multicenter studies 4 , 5 . Moreover, recent studies have suggested that the majority of cardiovascular events and all-cause mortality occurred among patients with non-obstructive CAD 5 , 13 . Thus, it is necessary to provide further risk stratification for the evaluation and management of non-obstructive CAD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our previous study has showed that the prevalence of non-obstructive CAD is higher than that of obstructive CAD 13 , which is consistence with other multicenter studies 4 , 5 . Moreover, recent studies have suggested that the majority of cardiovascular events and all-cause mortality occurred among patients with non-obstructive CAD 5 , 13 . Thus, it is necessary to provide further risk stratification for the evaluation and management of non-obstructive CAD.…”
Section: Discussionsupporting
confidence: 88%
“…This study population consisted of 5991 consecutive patients with suspected CAD who were performed coronary CTA for clinical reasons between June 2017 and December 2019 at two hospitals in Wuhan, China. We have previous reported the details of the rational of the study and included parts of the patients 13 . We used the first coronary CTA examination to characterize CAD extent if multiple coronary CTAs were performed during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…The coronary arteries with a diameter ≥2 mm were evaluated for luminal narrowing. The standardized Coronary Artery Disease-Reporting and Data System (CAD-RADS) classification was reported in our recent researches (14,18,20).…”
Section: Methodsmentioning
confidence: 99%
“…Observed vulnerable plaque in CCTA (modifier V in CAD-RADS) was not excluded, nor was it applied in the reporting since it was observed not to contribute incrementally to prognostic function [ 4 , 22 ]. Also, both CAD-RADS 4A and 4B were assessed as CAD-RADS 4, not as separate categories.…”
Section: Methodsmentioning
confidence: 99%
“…This system describes the maximal degree of coronary artery stenosis in percent as follows: CAD-RADS 0: 0%, CAD-RADS 1: 1–24%, CAD-RADS 2: 25–49%, CAD-RADS 3: 50–69%, CAD-RADS 4A: 70–99%, CAD-RADS 4B: left main > 50% or three-vessel obstruction, CAD-RADS 5: 100%. It has now been accepted as the standard method of reporting CCTA results, proven to be superior in diagnostic and prognostic aspects to previous methods [ 4 – 7 ].…”
Section: Introductionmentioning
confidence: 99%